DAKWAH PEMBANGUNAN SEBAGAI SEBUAH MODEL PEMBERDAYAAN MASYARAKAT PEDESAAN - Fajar, Muhammad Samson; Nur, Muhammad (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2020)
Development da'wah is a religious activity that encourages improvement and changes in the social system of the community so that the community is able to take the initiative and take initiative on the existing environmental potential, which in turn can improve the welfare of life. In achieving this welfare, da'wah can use two development models, namely, value oriented development and people centered development.Da'wah institutions apply the two models above by establishing partners with non-governmental organizations (NGOs) and government agencies as needed. Then, the development programs must be implemented in an integral manner, and must involve the participation of rural communities and jama'ah because the essence of this development da'wah is the community (jama'ah) as actors to empower themselves.